THE INFLUENCE OF HUMAN RESOURCE COMPETENCIES AND INTERPERSONAL COMMUNICATION ON SERVICE QUALITY AND ITS IMPLICATIONS FOR PUBLIC SATISFACTION AT THE WEST JAVA MANPOWER AND TRANSMIGRATION OFFICE - Nova Karlina; Farida Yuliaty; Sobarna Kartamihardja; Kosasih; Vip Pramarta (RADJA PUBLIKA, 2026)
Public services in the employment sector face increasingly complex challenges along with rising public demands for fast, transparent, and high-quality services. This condition is also evident in West Java Province, which has a large labor force and relatively high unemployment rate, placing the West Java Provincial Manpower and Transmigration Office (Disnakertrans) in a strategic yet highly pressured position. Although the Community Satisfaction Index indicates a very good category, there remains a gap between formal evaluations and the actual public perception of the services received. This study aims to analyze the influence of human resource competence and interpersonal communication on service quality and its implications for public satisfaction. The research employed an associative quantitative method with a cross-sectional design. A sample of 233 respondents was determined using the Slovin formula from a population of 553 service users. Data were collected through questionnaires and analyzed using path analysis with SPSS. The results show that human resource competence and interpersonal communication have a significant effect on service quality, and service quality has a significant effect on public satisfaction. Service quality is proven to mediate the effect of human resource competence and interpersonal communication on public satisfaction